P0543NQO1ATTENUATES RENAL INJURY BY RENAL ISCHEMIA REPERFUSION OF MICE. (6th June 2020) - Lee, Kang Wook; Jeong, Jin Young; CHOI, DAE EUN; Na, Ki Ryang; Kim, Haeri; Ham, Young Rok; Choi, Wonjung; Chang, Yoon-Kyung; JEON, JAE WAN
Abstract: Background and Aims: Ischemia-reperfusion (I-R)-induced reactive oxygen species (ROS) are thought to be a major factor in the development of acute renal injury by promoting the initial tubular damage. NAD(P)H:quinone oxidoreductase 1 (NQO1) is a well-known antioxidant protein that regulates ROS generation. We investigate whether NQO1 modulates the renal I-R injury. Method: C57BL/6N NQO1-deficient mice (NQO1/) were generated. Mice were sacrificed at 4, 12, 24, and 48 h after the surgical procedure. I-R was performed using vascular clamp for 30min. We analyzed renal function, oxidative stress, and tubular apoptosis after I-R injury. Results: NQO1/ mice showed increased blood urea nitrogen and creatinine levels, tubular damage, oxidative stress, and apoptosis. In the kidneys of NQO1/ mice, the cellular NADPH/NADPþ ratio was significantly higher and NOX activity was markedly higher than in those of NQO1þ/þ mice. The activation of NQO1 by β-lapachone (βL) significantly improved renal dysfunction and reduced tubular cell damage, oxidative stress, and apoptosis by renal I-R. Moreover, the βL treatment significantly lowered the cellular NADPH/NADPþ ratio and dramatically reduced NOX activity in the kidneys after IRI. From these results, it was concluded that NQO1 has a protective role against renal injury induced by I-R and that this effect appears to be mediated by decreased NOX activity via cellular NADPH/NADPþ modulation. Conclusion: NQO1 activation might be beneficial for ameliorating renal injury induced by I-R.